Uganda : Fifth Review Under the Policy Support Instrument and Request for Modification of Assessment Criteria; Staff Report; and Press Release. (IMF Staff Country Reports; Country Report ;, 2009)
This paper discusses key findings of the Fifth Review under the policy support instrument for Uganda. Strong fundamentals and prudent economic policies of the past give Uganda scope to implement measured countercyclical policies without undermining macroeconomic stability. Monetary policy has been gradually eased in the face of the dry-up in private external financing. In spite of the slowdown-induced shortfall in tax revenue, the fiscal authorities are committed to accelerate and improve execution of investment spending to provide a positive impulse to growth and remove critical bottlenecks.